The efficacy and safety of acupuncture for perimenopause symptom compared with different sham acupuncture control groups: A protocol of systematic review and meta-analysis. Issue 10 (March 2020) - He, Qiujun; Ren, Yajing; Wang, Yanqiu; Zhang, Feng; Zhang, Sanyin
Abstract: Background: Perimenopause is a period that every woman must go through, most people are more or less affected by perimenopausal symptoms, it to affect women's health, work, life, and economy. As acupuncture treatment is more and more increasing in perimenopausal symptoms, there have also been many clinical trials about it. But the results of the trials are inconsistent. Therefore, we will conduct a systematic review and meta-analysis of the safety and efficacy of perimenopausal symptoms treated with acupuncture. Methods: The protocol followed Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols. RCT study on different acupuncture interventions for perimenopausal symptoms will be searched in 8 databases (PubMed, EMBASE, the Cochrane Library, the web of science, CBM, CNKI, WAN FANG, and VIP). Besides, the search will also be performed on the clinical trial research platform if necessary. The primary outcome that will be extracted: the Flushes per 24 hours, the Frequency of hot flashes, the severity of hot flashes, the menopause-related symptom score, the treatment efficacy, the adverse event. Endnote software X8 will be used for study selection, STATA 13.0 and Review Manager software 5.3 will be used for analysis and synthesis. These studies selection, data extraction, and risk of bias assessment will be conducted by 2 independent reviewers. Results: This study will provide the results: 1. the primary and secondary outcome indicators of different acupuncture intervention measures (traditional hand acupuncture, moxibustion, ear acupuncture, laser, acupressure points) for perimenopausal symptoms. 2. The effects of different control groups (medicine control, routine care, waiting, and sham acupuncture control) on the analysis results will be reported, especially the effects of different sham acupuncture control (invasive/noninvasive) on the analysis results. Conclusion: This systematic review and meta-analysis study hopes to provide useful evidence for better use of different types of acupuncture in treat perimenopausal symptoms and better design of control groups in related clinical trials. In addition, the research conclusion will be published in peer journals. OSF REGISTRATION NUMBER DOI 10.17605/OSF.IO/VZCKU Ethics and dissemination This conclusion of the study will be published in peer journals. The ethical approval is not required because there is no direct involvement of human.